The Role of the Headmaster in Establishing Exemplary Schools - Indri Indri (STAI Hubbulwathan Duri, 2023)
This research analyzes the character of the madrasah principal in leading educational institutions. The objective of this study is to elucidate the significance of a madrasah head's virtuous character as a leader, which undoubtedly influences the persons and institutions under their guidance. This study is a qualitative case investigation conducted at a Madrasah located in Kartasura during the year 2022. Employing the interview technique with the headmaster, two educators, two parental figures of students, and observation. Triangulation is employed to verify the accuracy of the data by juxtaposing it with interviews and observations. This study employed interactive analysis. The findings of this investigation: The head of Madrasah embodies the qualities of uswatun hasanah, which include adherence to instructions, democratic leadership, and recognising teachers as individuals with their own capabilities. They possess excellent listening and speaking skills, empathy towards others, and the ability to make sound judgements. The term used to refer to this character is